Fracture Strength of Three-Unit Implant Supported Fixed Partial Dentures with Excessive Crown Height Fabricated from Different Materials - Vahideh Nazari; Safoura Ghodsi; Marzieh Alikhasi; Majid Sahebi; Ahmad Reza Shamshiri (Tehran University of Medical Sciences, 2017)
Objectives: Fracture strength is an important factor influencing the clinical long-term success of implant-supported prostheses especially in high stress situations like excessive crown height space (CHS). The purpose of this study was to compare the fracture strength of implant-supported fixed partial dentures (FPDs) with excessive crown height, fabricated from three different materials. Materials and Methods: Two implants with corresponding abutments were mounted in a metal model that simulated mandibular second premolar and second molar. Thirty 3-unit frameworks with supportive anatomical design were fabricated using zirconia, nickel-chromium alloy (Ni-Cr), and polyetheretherketone (PEEK) (n=10). After veneering, the CHS was equal to 15mm. Then; samples were axially loaded on the center of pontics until fracture in a universal testing machine at a crosshead speed of 0.5 mm/minute. The failure load data were analyzed by one-way ANOVA and Games-Howell tests at significance level of 0.05. Results: The mean failure loads for zirconia, Ni-Cr and PEEK restorations were 2086±362N, 5591±1200N and 1430±262N, respectively. There were significant differences in the mean failure loads of the three groups (P<0.001). The fracture modes in zirconia, metal ceramic and PEEK restorations were cohesive, mixed and adhesive type, respectively. Conclusions: According to the findings of this study, all implant supported three-unit FPDs fabricated of zirconia, metal ceramic and PEEK materials are capable to withstand bite force (even para-functions) in the molar region with excessive CHS.